The book club bible - Bible (London Michael O'Mara, 2007)
Every book club member has felt the pressure to pick out a new title for the whole group to read and enjoy. Wouldn't it be great if there was a book that helped you to make that all-important decision and maintain your place of respect in the book club? Fear no more, this comprehensive guide" "is here to help, shining an illuminating light on the treasures of the literary world, from "The Bell Jar "to" Brick Lane, Mrs. Dalloway "to "Middlesex. "Containing a diverse selection of books to choose from, the guide includes a non-spoiler synopsis, background information on the author, historical context, interesting discussion points and facts, and potential companion volumes. Compiled by a range of English literature experts and avid readers, this informative and enthusiastic guide is guaranteed to inspire."